Miseries behind Heroism: A Shadowed Part of the Gurkhas in Farwell’s The Gurkhas - Rai, Ram Prasad (Tribhuvan University Journal, 2021)
This paper explores and analyzes the miseries, anguish, and hardships experienced by the Gurkhas and their families that are masked by their worldwide name and fame of their bravery in Byron Farwell’s The Gurkhas. The writer presents the bravery, dedication and loyalty exhibited by the Gurkhas in the Anglo-Nepal War (1814-16) that attracts the British administration. Despite the defeat of the Gurkhas, the British institution begins to enroll them into their army. Their heroic combat experiences play an important role in the success of Britain’s imperial movement around the world. They fought and got victory in many ways for Britain along with the First (1914-18) and Second (1939-45) World Wars. Moreover, the writer also discusses the discomforts, sufferings and agonies that the Gurkhas and their families went through before, during and after the wars. As this study is based on the qualitative research method, the researcher has consulted library for the related books, journal articles and internet support extensively. Some historians as well as the ex-British Gurkhas, who had been in wars for Britain, also have been consulted for further ideas. The research study is significant because it educates people about various problems faced by the Gurkhas and their families hidden behind the myth of their heroism.